The evolution of survival of pulmonary arterial hypertension over 15 years. (18th October 2022) - Hendriks, Paul M.; Staal, Diederik P.; van de Groep, Liza D.; van den Toorn, Leon M.; Chandoesing, Prewesh P.; Kauling, Robert M.; Mager, Hans‐Jurgen; van den Bosch, Annemien E.; Post, Marco C.; Boomars, Karin A.
Abstract: The prognosis of pulmonary arterial hypertension (PAH) remains dismal. Over the years, multiple therapeutic advances have been introduced. This study evaluates the evolution of PAH survival over the past 15 years. We included 293 consecutive adult patients diagnosed with PAH between 2005 and 2019 (median age: 61.8 years, 70.3% female). Patients were divided into three cohorts based on the time of diagnosis: 2005–2009, 2010–2014, and 2015–2019 (2005–2009: n = 56; 2010–2014: n = 111; 2015–2019: n = 126). Transplant‐free survival was measured from the date of right heart catheterization until patients reached the composite endpoint of lung transplant or death. Multivariable cox‐pulmonary hypertension regression was used to study the effect of the time of diagnosis. The final cox model was fitted in both younger and older patients to evaluate the difference between these groups. During a median follow‐up time of 4.1 (interquartile range: 2.2–7.3) years, 9 patients underwent lung transplantation and 151 patients died. The median overall transplant‐free survival was 6.2 (5.5–8.0) years. Patients older than 56 years at baseline who were diagnosed in 2005–2009 showed better survival compared to patients diagnosed in 2010–2014 and 2015–2019 with an adjusted hazard ratio of, respectively, 2.12 (1.11–4.03) and 2.83 (1.41–5.69). Patients younger than 56 years showed neither an improved nor deteriorated survival over time. In conclusion, survival in patients with PAH did not improve over time, despite more available therapeutic options. This might be partly due to the changed demographic characteristics of the PAH patients and a still important diagnostic delay.